Kiai Leadership in Empowering the Independent Enterprises of Pesantren - Badrut Tamam; Titi Kadi (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study aims to analyze the role of Kiai leadership in empowering independent businesses at two pesantren: Al Azhar Pesantren in Balikpapan and Salsabila Pesantren in Samarinda. The main focus of this research is to examine how Kiai leadership influences the management and development of independent businesses at both pesantren, as well as the factors that support the success of these ventures. The research method employed is a qualitative approach with in-depth interviews and participatory observation techniques. Data were collected from the Kiai, independent business managers, and students (santri) at both pesantren. The results show that Kiai leadership significantly influences strategic decision-making, motivation, and the entrepreneurial culture applied in the independent businesses of the pesantren. Leadership based on values of independence, role modeling, and individual empowerment plays a key role in developing independent businesses that contribute to improving the welfare of the pesantren and its students. Furthermore, this study also finds that support from the surrounding community and cooperation with various stakeholders contribute to the success of the independent businesses. Therefore, Kiai leadership can be seen as an important factor in optimizing the resource potential of the pesantren and realizing economic independence within the pesantren environment.